Mind-muscle connection training principle: influence of muscle strength and training experience during a pushing movement - Calatayud, J.; Vinstrup, J.; Jakobsen, M. D.; Sundstrup, E.; Colado, J. C.; Andersen, L. L. (European Journal of Applied Physiology, 2017)
Purpose: To investigate the effect of different attentional focus conditions on muscle activity during the push-up exercise and to assess the possible influence of muscle strength and training experience. Methods: Eighteen resistance-trained men performed 1RM bench press testing and were familiarized with the procedure during the first session. In the second session, three different conditions were randomly performed: regular push-up and push-up focusing on using the pectoralis major and triceps brachii muscles, respectively. Surface electromyography (EMG) was recorded and analyzed (EMG normalized to max; nEMG) for the triceps brachii and pectoralis major muscles. Results: Participants had on average 8 (SD 6) years of training experience and 1RM of 1.25 (SD 0.28) kg per kg bodyweight. Focusing on using pectoralis major increased activity in this muscle by 9% nEMG (95% CI 5-13; Cohen`s d 0.60) compared with the regular condition. Triceps activity was not significantly influenced by triceps focus although borderline significant, with a mean difference of 5% nEMG (95% CI 0-10; Cohen`s d 0.30). However, years of training experience was positively associated with the ability to selectively activate the triceps (ß = 0.41, P = 0.04), but not the pectoralis. Bench press 1RM was not significantly associated with the ability to selectively activate the muscles. Conclusion: Pectoralis activity can be increased when focusing on using this muscle during push-ups, whereas the ability to do this for the triceps is dependent on years of training experience. Maximal muscle strength does not appear to be a decisive factor for the ability to selectively activate these muscles.